Magnetic Characteristics and Microstructure of Some Ferrite Antenna and Inductor Cores Doped with Co, Ca, and Si - Loh, Pit Mui (1996)
This work gives accounts of an attempt to produce two types of commercial ferrite material whose magnetic characteristics were to be studied in relation to some additives and the microstructure. Two compositions, MgZn- and NiZn-based ferrites, were prepared by the oxide method and characterised mainly in terms of magnetic properties and microstructure. The former composition was to be used as the material for antenna bars and the latter for high-frequency inductors. The antenna material was shaped into bars and toroids while the inductor material into rectangular plates and toroids. The properties of the two compositions were investigated as functions of the amount of additives (CaD and Si02 and CoO). The influence of sintering temperature and forming pressure on magnetic and mechanical properties and average grain size was also studied. The experimental investigation consists of three parts. Firstly, various compositions of MgZn-based territes were prepared and the properties upgraded by suitable additions of CaO and SiOl. The inexpensive raw material powder MgO was used to substitute NiO in a composition of commercial NiZn-based ferrite commonly used for antenna bars. A MgZn-territe composition with properties matching the commercial material's properties was successfully obtained. Secondly, the effect of directly-added CoO to MgZn- and NiZn-based ferrites was studied. The addition of CoO for these two original compositions decreased the initial permeability and minimised the variation of initial permeability with temperature. However. the frequency range and the Curie temperature increased with the increase of CoO content. The variations of the properties as a function of the amount of CoO were discussed in tenns of the contribution of C0²⁻ ions to magnetocrystalline anisotropy. Thirdly, intentional changes of microstructure for both original compositions were made by varying the forming pressure and sintering temperature. No significant changes on magnetic and mechanical properties and microstructure were found with the increase of forming pressure. However, the average grain size increased with the sintering temperature, thus, influencing the magnetic and mechanical properties of the samples. The initial penneability increased linearly with grain size.